STUDENT'S RESPONSE THROUGH THE USE OF ONLINE CROSSWORD PUZZLE TO IMPROVE CRITICAL THINKING IN LEARNING ENGLISH - Joko Prayudha.S (PRIMACY Journal of English Education and Literacy, 2023)
The development of game-based learning technology is one of the advancements in innovation in the field of education. Teachers can take advantages of this opportunity to help students to improve their critical thinking skills while learning English. The application of game-based learning that can be used to improve critical thinking skills in this study is the online crossword puzzle. The current study aims to reveal students' responses to the use of digital-based learning applications in improving students' critical thinking skills when learning English. The method used is qualitative through a descriptive approach. Data obtained through field observations and interviews. After that, the data was analyzed through data reduction, data display, and conclusion. The results of the study showed that the students' responses when learning English through online crossword puzzles were very positive. Students' enthusiasm for learning is increasing, and there is an increase in student interest and motivation when implementing these applications in English classes so that students can develop self-confidence when doing English assignments better.